The evolution of massive disc galaxies with environment and redshift - Bamford, Steven Peter (2006)
This thesis examines the evolution of massive disc galaxies as a function of cosmic time and environment by analysing a sample of luminous disc galaxies, located in the field and rich clusters at intermediate redshifts. The data utilised for this study are two-dimensional optical spectra obtained with the FORS2 instrument on the VLT, along with imaging from a variety of sources. From these we measure absolute rest-frame B-band magnitudes, stellar scalelengths (r_d,phot), rotation velocities (V_rot), emission-line scalelengths (r_d,spec) and emission-line equivalent widths, resulting in estimates of gas-phase oxygen abundance, current star formation rate (SFR) and dust extinction.